Use of Paper Mode Quizizz Media to Increase Learning Motivation of Grade IV Students of SD Negeri 1 Manislor - Nur Aulia, Wirda; Sudrajat, Sudrajat; Hidayatullah, Syarif (Annpublisher, 2024)
This research was motivated by the low level of motivation of students to learn. Based on the results of observations, there are eight students with low learning motivation criteria and ten students with moderate learning motivation level criteria. Based on this, the research aims to increase the learning motivation of fourth-grade students in Natural and Social Sciences subjects. The Kemmis & Taggart spiral model includes this research in classroom action research. The data collection techniques in this study include observation and FGD (Focus Group Discussion). The research was conducted collaboratively with field supervisors and class teachers. Based on the results of the FGD, an agreement was obtained to use paper mode quizizz media to solve the problem of increasing students' low learning motivation. The research was carried out through pre-cycle, cycle 1, and cycle 2. One cycle includes planning, implementation, observation, and reflection stages. The research subjects were fourth-grade students of SDN 1 Manislor, totaling 17 people. In pre-cycle research, the percentage obtained was 50% and increased by 84% in cycle 2. Based on these percentage results, the use of paper-based quizizz media can increase the learning motivation of fourth-grade students of SDN 1 Manislor